'Monetary and Fiscal Rules in an Emerging Small Open Economy' - Levine, Paul (IMF Working Papers; Working Paper ;, 2009)
We develop a optimal rules-based interpretation of the 'three pillars macroeconomic policy framework': a combination of a freely floating exchange rate, an explicit target for inflation, and a mechanism than ensures a stable government debt-GDP ratio around a specified long run. We show how such monetary-fiscal rules need to be adjusted to accommodate specific features of emerging market economies. The model takes the form of two-blocs, a DSGE emerging small open economy interacting with the rest of the world and features, in particular, financial frictions It is calibrated using Chile and US data. Alongside the optimal Ramsey policy benchmark, we model the three pillars as simple monetary and fiscal rules including and both domestic and CPI inflation targeting interest rate rules alongside a 'Structural Surplus Fiscal Rule' as followed recently in Chile. A comparison with a fixed exchange rate regime is made. We find that domestic inflation targeting is superior to partially or implicitly (through a CPI inflation target) or fully attempting to stabilizing the exchange rate. Financial frictions require fiscal policy to play a bigger role and lead to an increase in the costs associated with simple rules as opposed to the fully optimal policy.